Evaluación de nuevas alternativas terapéuticas naturales para el tratamiento de la endometriosis - Ferella, Luciana (2018)
Endometriosis is characterized by the presence of endometrial tissue outside the uterine cavity. Current therapies are inefficient and carry several adverse effects. Our objective was to evaluate the effect of carnosic acid (CA) and rosmarinic acid (RA), compounds found in Rosmarinus officinalis and of wogonin (WG), an active constituent of Chinese herbal medicine, on experimental endometriosis models. CA 10?g/ml; RA 100?g/ml and WG 80?M inhibited endometrial stromal cells proliferation in primary cultures and in the endometrial T-HESC cell line (p<0.05). Moreover, CA and WG induced cell cycle arrest at the G2/M phase (p<0.01) but apoptosis was not augmented. WG reduced ER? expression in T-HESC (p<0.01), however estradiol secretion was not altered. Furthermore, RA reduced intracellular ROS accumulation (p<0.001) while WG increased them, suggesting a pro-oxidant effect (p<0.05). On a mast cell line, CA and WG regulated the expression of genes involved in G2/M cell cycle progression. In-vivo, CA 20mg/kg/day, RA 3mg/kg/day and WG 20mg/kg/day reduced endometriotic-like lesions size (p<0.05). All compounds decreased the percentage of cells in proliferation (p<0.05), while AR and WG increased the percentage of apoptotic cells in murine endometriotic-like lesions (p<0.05). These findings are promising and support further investigation of these compounds as new therapeutics for endometriosis.